Mimicking characteristics of cast iron for enhanced electrocatalytic dehydrogenation of methane - Verma, Tushar Singh; Devi, R. Nandini; Krishnamurty, Sailaja (Fuel, 2025)
Enhancing the efficiency of methane dehydrogenation through chemical modification of electrocatalytic iron surfaces with impurities that resemble cast iron properties is demonstrated computationally using Density Functional Theory methodologies. Investigating methane dehydrogenation on thermally stable Fe surfaces with discrete planes and anchoring impurities such as Al, C, and Si minimized reduction barriers. Electrochemical treatment of methane on these robust surfaces yields clean hydrogen and carbon-based compounds, such as carbon nanomaterials and carbon black. As for the most efficient active sites for enhanced methane dehydrogenation, the active plane 100 with 5.5 % C impurities and 0.51 eV reduction barrier is determined to be the most dependable, followed by the active plane 110 with 5.5 % Si impurities and the lower 0.98 eV reduction barrier. Utilizing CI-NEB (Nudged Elastic Band), the dissociation barrier investigation established the electrolytic catalysts' performance. This work paves the way for experimentalists and demonstrates the economic viability of Fe-based catalysts for the Catalytic Dehydrogenation of Methane.
Keywords: carbon black; Density Functional Theory (DFT); Dry methane reforming (DMR); Electrochemical methane dehydrogenation; Fe surface catalyst